pendidikan anak tentang aqidah mengenal allah swt - Aminulloh, Shofi (Maliki Interdisciplinary Journal, 2025)
Aqidah education is a fundamental cornerstone in shaping a child’s character and spirituality from an early age, especially in introducing them to Allah SWT. This abstract discusses the importance of introducing the concepts of Tawhid (Oneness of God) and the obligatory attributes of Allah SWT to children using engaging and easily understandable methods. The approaches used include stories, games, songs, and real-life examples from the universe to help children grasp the uniqueness, majesty, and love of Allah SWT. The primary goal of this education is to instill a sense of love, awe, and fear directed solely towards Allah SWT, and to build a strong conviction as a foundation for living life. Through this, it is hoped that children will grow into individuals with noble character, a solid Islamic identity, and a continuous feeling of closeness to the Creator.